Sosialisasi Penggunaan Moda Transportasi Darat dan Udara Dimasa Pandemi COVID 19 - Rudy; Pamuraharjo, Hemi; Arti, Endang Sugih; Praptiningsih, Nunuk; Sadiatmi, Rini (Jurnal Pengabdian Kepada Masyarakat, 2021)
Transportation or people travel, this term used by Gugug Tugas Percepatan Penanganan Covid-19 is people mobility from area to another area with administrative boundry as province/district/city and arrival form abroad (repatriation) enter the territory of Republikc of Indonesia by using prival vehicle or public transport land/railways/sea and by air. The provisons of land transportation and air transportation to be regulated for the effort of Covid-19 accelartion handling be realized and in other hands the piepole mobility still on going for the purpose of the run of economics. How this can be run side by side ?. of course there are a matters to be adjust, for example about behavior of trasnportaion service user that shall be adjust to new protocol in pandemic periode that different with normal behavior. From transportation operator side also adjust required, Beside of new protocol how to embark and disembark people the capacity of transportation vehicle adjust required also and can not be used according to manufacturer spesifications. This matter not so easy for the user or transportation operator relating to investment and operational of trasnprtation operator. In this community service focused to how to reached equilibrium between pandemic handling effort and the economy from land transportation and air transportation point of view.